PENGARUH ALAT HEMAT ENERGI LISTRIK KOMERSIAL PADA SISTEM KELISTRIKAN RUMAH TANGGA - , YB. Praharto, ST, Ir. T. Haryono, M.Sc., CEng., MIET ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Having widely spread the energy saver tools, wich is called energy saver, promoted to save electrical energy used in residential areas should be studied. That tools are packed in enclosed box and marketed with no itâs detail component. In this study, did by laboratory standard. that tools is considered as a black box, parallel installed with severally load variation that is used in residence, as resitif's loads, inductive and capasitif loads. it was intended to explore itâs characteristic to prove what it was said to make electrical energy usage more efficient using energy saver to get useful data to know there is don't it that energy saver's influence to PLN'S electric network recidence Electrical parameters needed were. Active power (P), apparent power (S), reactive power (Q), voltage (V), current (I), power factor (CosÏ), total impedance (ohm), frequency (f), voltage harmonic and current harmonic, which measured before and after the energy saver installed. Futher, curve fittings which describe the characteristics of resitif, inductive and capacitive loads, were in order to fit the energy save characteristic in the effort to prove itâs energy saving, used to calculate the effect of the use of energy saver is on the grid for the household.